Designing green landscapes - Gadow, Klaus von; Pukkala, Timo ([Dordrecht, The Netherlands] Springer, 2008)
Adaptive Design of Forested Landscapes / Klaus von Gadow, Tuula Nuutinen, Seppo Kellomaki -- Landscape Metrics, Scales of Resolution / Samuel A. Cushman, Kevin McGarigal -- Detailed Assessment Using Remote Sensing Techniques / Petteri Packalen, Matti Maltamo, Timo Tokola -- Assessing Landscape Attributes / Christoph Katsch -- Spatial Optimisation - Computational Methods / Pete Bettinger, Young-Hwan Kim -- Integrating Multiple Services in the Numerical Analysis of Landscape Design / Timo Pukkala -- Decentralized Forest Planning Models - a Cellular Automata Framework / Anne-Helene Mathey, John Nelson -- Coordinating Management Decisions of Neighboring Stands with Dynamic Programming / Howard Hoganson, Jose G. Borges, Yu Wei -- Designing a Forested Landscape in Finland Under Different Climate Scenarios / Jordi Garcia-Gonzalo, Manfred J. Lexer, Heli Peltola, Seppo Kellomaki -- Visualization in the Design of Forested Landscapes / Andre O. Falcao -- Visualization in Support of Landscape Design / Rudiger Mach.
Includes bibliographical references.
Keywords: Forest management